Efektivitas Modul Inkuiri Dengan Strategi Konflik Kognitif Dalam Meningkatkan Keterampilan Berpikir Kritis Mahasiswa - Pahriah, Pahriah; Hendrawani, Hendrawani (Hydrogen: Jurnal Kependidikan Kimia, 2020)
The purpose of this study is to evaluate the effectiveness of the application of inquiry modules with cognitive conflict strategies in chemical bonding material in improving students’ critical thinking skills. This research is a quantitative descriptive study that was carried out with the design of one group pretest posttest. The sample used was 26 students who took general chemistry courses with a purposive sampling technique. Data were analyzed by normalized N-gain method and paired samples t-test. The result of this study showed that average N-gain of student critical thinking skill after application of inquiry modules with cognitive conflict strategies is 0.6 with medium category. Average score of student critical thinking skill after treatment (74,12) is significantly higher than before (35,77) that proved by t statistic (41,09) higher than t critic (1,71) with df = 25 and p = 0,000 on one tail t-test. Therefore, it was concluded that the application of inquiry modules with cognitive conflict strategies enhance student critical thinking skill on chemical bonding material learning effectively.